Response to sulfur in Schizosaccharomyces pombe. Issue 5 (19th July 2021) - Ohtsuka, Hokuto; Shimasaki, Takafumi; Aiba, Hirofumi
ABSTRACT: Sulfur is an essential component of various biologically important molecules, including methionine, cysteine and glutathione, and it is also involved in coping with oxidative and heavy metal stress. Studies using model organisms, including budding yeast ( Saccharomyces cerevisiae ) and fission yeast ( Schizosaccharomyces pombe ), have contributed not only to understanding various cellular processes but also to understanding the utilization and response mechanisms of each nutrient, including sulfur. Although fission yeast can use sulfate as a sulfur source, its sulfur metabolism pathway is slightly different from that of budding yeast because it does not have a trans-sulfuration pathway. In recent years, it has been found that sulfur starvation causes various cellular responses in S. pombe, including sporulation, cell cycle arrest at G2, chronological lifespan extension, autophagy induction and reduced translation. This MiniReview identifies two sulfate transporters in S. pombe, Sul1 (encoded by SPBC3H7.02) and Sul2 (encoded by SPAC869.05c), and summarizes the metabolic pathways of sulfur assimilation and cellular response to sulfur starvation. Understanding these responses, including metabolism and adaptation, will contribute to a better understanding of the various stress and nutrient starvation responses and chronological lifespan regulation caused by sulfur starvation. Abstract : This mini review summarizes the latest sulfur metabolism mechanism and starvation response along with sulfate transporters identification in the fission yeast Schizosaccharomyces. pombe .